Laparo-therapy for acute omental torsion - Case report with review of literature - Kaur, Ravneet; Joshi, Abhijit Sharadchandra (Indian Journal of Case Reports, 2025)
Omental torsion is a rare event. Often, it mimics other more common conditions like appendicitis. Most of the time, it is diagnosed incidentally during surgery being performed purportedly for some other more common condition. It can be managed easily by laparoscopy with the same ergonomic trocar positions. We, herein, report the case of a 33-year-old female patient who was diagnosed preoperatively to have acute appendicitis but turned out to have a normal appendix and an acute torsion-gangrene of the greater omentum, instead. The same was treated laparoscopically. The patient had an uneventful postoperative recovery.